2017
DOI: 10.1186/s41935-017-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex and age for Egyptians using computed tomography of the first lumbar vertebra

Abstract: Background: Identification of bony remains and other decomposed parts of human is of great importance not only for legal but also for humanitarian reasons. However, in certain instances due to burial factors or in cases of explosion disasters, many of large bones may be destroyed or incomplete. For age and sex identification, vertebrae aren't well studied; however, many vertebrae showed high accuracy rates for sex identification. Methodology: One hundred and twenty-three Egyptian patients were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Depending on IgG optical densities' values combined with the existence of larval stage, the results showed that infested and non-infested animal cases could be distinguished from each other all over the winter season as the infested cases were constantly detected. This finding might confirm previous results [3,6] where the larval stage was established and the optical densities' values were increasing gradually during the winter season. This result was likeminded with activity of adult fly which began in December so, specific IgG levels were found to be sharply increased and positively interact with developing L2 and/or L3 larvae.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Depending on IgG optical densities' values combined with the existence of larval stage, the results showed that infested and non-infested animal cases could be distinguished from each other all over the winter season as the infested cases were constantly detected. This finding might confirm previous results [3,6] where the larval stage was established and the optical densities' values were increasing gradually during the winter season. This result was likeminded with activity of adult fly which began in December so, specific IgG levels were found to be sharply increased and positively interact with developing L2 and/or L3 larvae.…”
Section: Discussionsupporting
confidence: 82%
“…Rhinoestrosis is a parasitic diseasethat impairs equids' welfare and performance of infested animals, resulting in significant economic losses [3].Studies on Rhinoestrus spp. infesting donkeys in Egypt are scanty [6], without any documentation of its hematological, oxidative stress and pathological features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Sex can be estimated from first lumbar vertebra with reasonable accuracy in medico-legal cases when skeletal remains are incomplete. 11…”
Section: Introductionmentioning
confidence: 99%